FORMULATION AND REFORMULATION OF PUBLIC POLICY (CASE STUDY OF LAW NUMBER 11 OF 2020) - Sinaga, Budiman NPD; Hutahaean, Marlan; Hutabarat, Bonita Minarti E.; Pasaribu, Johnson (NOMOI Law Review, 2025)
The stage of formulating policy problems (problem structuring) is important in public policy. To produce new and more effective policies, expanding existing policies is very important. The evaluation must answer the contribution of a series of existing policies to improve the fulfilment of citizens' rights and obligations. This research uses normative research with a statute approach. The formulation of public policies in Law Number 11 of 2020 concerning Job Creation is carried out by the omnibus law method with the characteristics of reformulating, negating, and revoking part or all the other regulations. Public policy in Law Number 11 of 2020 concerning Job Creation must be reformulated because it conflicts with the techniques of drafting applicable laws and regulations as stipulated in various laws and regulations, especially Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. Along with the development of science, the use of new methods in formulating public policies is a necessity and even a necessity. However, the use of the new method needs to be initiated by socialization and regulation in laws and regulations related to public policy formulation. Further research needs to be carried out on the formulation and reformulation of public policies in the regions because regional needs are not necessarily with national needs.